Factor IX antibodies and tolerance in hemophilia B in the Nordic countries – The impact of F9 variants and complications. Issue 217 (September 2022) - Kihlberg, Kristina; Baghaei, Fariba; Bruzelius, Maria; Funding, Eva; Holme, Pål Andre; Lassila, Riitta; Martin, Myriam; Nummi, Vuokko; Ranta, Susanna; Strandberg, Karin; Andersson, Nadine Gretenkort; Berntorp, Erik; et al.
Abstract: Introduction: The development of inhibitory antibodies (inhibitors) in persons with hemophilia B (PwHB) causes significant morbidity. Data on the impact of the F9 variant and immune tolerance induction (ITI) outcome are limited. The aim of this study was to investigate the presence of neutralizing and non-neutralizing antibodies (NNA) in severe hemophilia B (HB) and to evaluate ITI outcome and complications in relation to the pathogenic F9 variant. Materials and methods: Persons with severe HB in the Nordic countries were enrolled and information on F9 variants, inhibitors, ITI and complications were collected. Analyses of anti-FIX antibodies with a fluorescence-immunoassay (xFLI) and an ELISA method were conducted. Results: Seventy-nine PwHB were enrolled. Null variants were seen in 33 (42 %) PwHB and 12 (15 %) had a current or former inhibitor. Eleven (92 %) of the inhibitor patients had experienced allergic manifestations and three (25 %) nephrotic syndrome. Of 10 PwHB with at least one ITI attempt, eight (80 %) were considered tolerant at enrolment. Immunosuppression was included in seven of eight successful or partially successful attempts. Five PwHB had at least one ITI failure before a successful or partially successful ITI. No NNA could be identified. Conclusion: A high proportion of severe F9 gene defects among persons with severe HB in the Nordic countries may explain the observed relatively high prevalence of inhibitors. ITI success was independent of the F9 variant and attained despite allergic manifestations and previous ITI failures. Inclusion of immunosuppression tentatively enhances the chances of ITI success. No NNA were observed.